Apakah Aglomerasi Ekonomi di Daerah Pedesaan Meningkatkan Perekonomian Lokal di Indonesia? - Erna Setianingsih; Khoirunurrofik (Jurnal Bina Praja, 2025)
Integrated rural areas development is strategically bolstering the success of equitable development in Indonesia. According to Village Law, rural areas are defined as clusters of villages with geographical proximity, similar superior commodities, common purpose, and government support in overcoming various basic issues, including expanding economic scale. Complying with the policy, this study aims to analyze the economic growth of rural areas, which focus on 62 National Priority Rural Areas as stated in the 2020–2024 National Medium Term Development Plan. The spatial analysis method examines intra-regional impacts on the increase of Village Original Income (VOI) as a result of economic agglomeration utilizing panel data at the village level. According to the findings, there is a considerable spatial correlation or positive spillover impact among the nearby villages in rural areas, which may further enhance and strengthen local economies. Additionally, the PSM-DiD method is applied to investigate whether the National Priority Rural Areas Development Policy influences the growth of VOI. However, the result hasn't yielded any convincing evidence of the beneficial effects of policy implementation in a short period. Despite the interaction result being frequently positive, it is unclear whether this policy drives the increase of VOI in rural areas significantly. Progressive intervention is needed from the governments at every level, from planning and implementation to evaluation. Besides, collaboration between different stakeholders, including the private sector and off-takers, is necessary to expedite the growth of the local economies and boost regional productivity.